Pesantren's Image in The Digital Age: A Netnographic Study on Viral Violence Cases and Institutional Reforms in Lombok - Jamaludin, Jamaludin; Malik, Abdul (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
This study investigates how digital communities perceive and respond to the increasing cases of sexual and physical violence in pesantren, with a focus on viral incidents in Lombok. The research specifically aims to examine two core aspects: the formation of public opinion in digital spaces and the emerging demands for institutional reform in pesantren. Using a qualitative approach with a netnographic method, the study analyzes social media content, including comments, videos, and online discourse from platforms such as TikTok, Facebook, and Instagram. Data were processed using the Huberman and Miles analysis technique. The findings reveal that viral cases have significantly damaged the pesantren’s public image, leading to widespread skepticism about their credibility and safety. The study concludes that pesantren must adopt transparent governance and proactive communication strategies to restore public trust. This research provides critical insight into how digital narratives shape institutional reform in Islamic education.